A New Planar Multiband Antenna for GPS, ISM and WiMAX Applications - I. Zahraoui; A. Errkik; M. C. Abounaima; A. Tajmouati; L. E. Abdellaoui; M. Latrach (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper a design of a new antenna with modified ground plane is validated for multiband applications. The proposed modified ground structure is incorporated with a patch antenna to boost the performance. The antenna’s entire area is 59.5x47mm2 and is printed on an FR-4 substrate and fed by a 50 Ohm microstrip line.  This structure is validated in the GPS (1.56-1.58 GHz) band at 1.57 GHz, in the ISM (2.43-2.49 GHz) band at 2.45GHz and in the WiMAX (3.50-3.56 GHz) band at 3.53 GHz. These three frequency bands have good matching input impedance for, S11≤-10 dB. The antenna presents a good performance in terms of radiation pattern, and it is designed, optimized, and miniaturized by using CST-MW whose results are compared with other solvers HFSS and ADS. The results obtained by the use of the three EM solvers are in good agreement. After realization, we have tested and validated this antenna. The measurement results of the antenna present a good agreement with the numerical results.